Characterisation of probiotic fermented milks produced from goat milk containing low or high somatic cell counts - Cem Karagözlü; Özer Kınık; A. Sibel Akalın; Harun Kesenkaş; Nayil Dinkçi (Mljekarstvo)
Probiotic fermented milks were produced from goat milk containing two different somatic cell counts (SCC) at low (<500.000 cells/mL) and high (>1.500.000 cells/mL) levels. The produced samples were analysed for some chemical, textural, microbiological and sensory properties. The samples made from high SCC goat milk had higher lipolytic activity. The viscosity and hardness of probiotic fermented milks with low SCC were higher than that of the higher SCC samples. Probiotic fermented milks produced with low SCC achieved higher sensory scores and the viability of the starter bacteria was more stable in these samples.